Deivida Zeina Meirovica un Alana Korkosa “Noziegums un sods”: Dostojevska daiļdarba transformācija grafiskajā romānā. - Fedosovs, Igors (Latvijas Universitāte, 2018)
Bakalaura darbs veltīts F. Dostojevska grāmatas “Noziegums un sods” transformācijas grafiskajā romānā izpētei. Atklājas komiksa kā kreolizēta teksta īpatnības un tiek veikta daiļdarbu salīdzinošā analīze. Pastiprināta uzmanība tiek veltīta varas motīvam Dostojevska romānā un tā transformācijai komiksā.

The bachelor paper is devoted to the research of transformation of the book «Crime and Punishment» by F.M. Dostoevsky into a graphic novel. The features of the comic book as creolised text are revealed, and comparative analysis of both works is performed. Special attention is paid to the motive of the power in the novel by Dostoevsky and its transformation in the comic book.
"Crime and Punishment" by David Zane Mairowitz and Alain Korkos: The Transformation of Dostoyevsky's Work into the Graphic Novel.
Keywords: Valodniecība; комикс; графический роман; креолизованный текст; Ф.М. Достоевский «Преступление и наказание»; мотив власти